Immediate Voice and Swallowing Complaints Following Revision Anterior Cervical Spine Surgery. (October 2020) - Strohl, Madeleine P.; Choy, Winward; Clark, Aaron J.; Mummaneni, Praveen V.; Dhall, Sanjay S.; Tay, Bobby K.; Loftus, Patricia A.; El-Sayed, Ivan H.; Russell, Matthew S.
Objective: To report on the incidence of dysphagia, dysphonia, and acute vocal fold motion impairment (VFMI) following revision anterior cervical spine surgery, as well as to identify risk factors associated with acute VFMI in the immediate postoperative period. Study Design: Retrospective cohort study. Setting: Tertiary care center. Subjects and Methods: All patients who underwent 2-team reoperative anterior cervical discectomy and fusion (ACDF) were retrospectively reviewed. Incidence of dysphonia, dysphagia, and acute VFMI was noted. Patient and operative factors were evaluated for association with risk of acute VFMI. Results: The incidence of postoperative dysphonia and dysphagia was 25% (18/72) and 52% (37/72), respectively. The incidence of immediate VFMI was 21% (15/72). Subjective postoperative dysphonia (odds ratio, [OR] 8; 95% CI, 2.2-28; P = .001) and dysphagia (OR, 22; 95% CI, 2.5-168; P = .005) were significantly associated with increased risk of VFMI. Three patients with VFMI required temporary injection medialization for voice complaints and/or aspiration. Infection (OR, 14; 95% CI, 1.4-147, P = .025) and level C7/T1 (OR, 5.5; 95% CI, 1.3-23, P = .02) were significantly associated with an increased risk of acute VFMI on multivariate logistic regression analysis. Number of prior surgeries, laterality of approach, side of approach relative to prior operations, and number of levels exposed were not significant. Conclusion: Early involvement of an otolaryngologist in the care of a patient undergoing revision ACDF can be helpful to the patient in anticipation of voice and swallowing changes in the postoperative period. This may be particularly important in those being treated at C7/T1 or those with spinal infections.